Bioenergy production in Finland and its effects on regional growth and employment - Antti Simola; Jouko Kinnunen; Hannu Törmä; Jukka Kola (Leibniz Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2010)
Finnish national climate and energy strategy sets the share of renewables in energy use to 38%, and a significant amount of this should be covered by biomass based energy. In 2020 forestry is set to contribute 24 TWh and agriculture 4-5 TWh to energy production. In particular, bioenergy resources are considerable in the rural areas. However, the regional aspects have gone without investigation before this study. This study is a general equilibrium analysis. We considered only the by-products and waste material from agriculture and forestry as the resources for bioenergy, and only heat and power production were considered as the potential end uses. A regional CGE-model (RegFinDynBio) was used to analyse the impact of increased use of bioenergy potential. Increase in bioenergy use will lower the levels of GDP and employment marginally but will, nevertheless, help to achieve the emission reduction goals. However, the regional results showed the uneven distribution of the costs. The regions that beforehand seemed to be the most promising ones fared the worst. Southern Ostrobothnia was the sole exception, because of its bioenergy export income. The greatest difficulties are seen in Kainuu. Eastern Uusimaa shows significant losses as well, but they can be traced back to the region's economic structure, which is heavily dependent on fossil fuel refining industries. Some regions that use gas as energy source are seen to gain marginally because of their more diverse energy production system.
Keywords: 330; bioenergy; agriculture and forestry; regional economy; growth; employment; CGE-modelling